Prioritizing syphilis control: Now is the time for action - Tucker, Joseph D.; Marley, Gifty; Marks, Michael; Mabey, David (Frontiers in Medicine, 2022)
Syphilis control programs and research received fewer resources and attention compared to HIV and other sexually transmitted infections (STIs) in the pre-pandemic era. The neglect of syphilis within comprehensive STI control efforts may be related to diagnostic (poor diagnostics), historical (legacies of racism in research), public health (limited partner services), and social problems (limited public engagement). At the same time, there are increasingly compelling reasons to prioritize syphilis control programs and research by harnessing lessons learned and advances during COVID-19. The closure of many STI facilities has accelerated new syphilis diagnostic pathways (e.g., syphilis self-testing), providing new ways for people to be screened outside of clinics. COVID-19 has underlined health inequities that fuel syphilis transmission, providing an opportunity to reckon with the historical legacy of racism that is linked to syphilis research. COVID-19 partner tracing efforts have also contributed to additional resources for partner services which may enhance syphilis control efforts. Finally, COVID-19 has demonstrated the importance of public engagement, making the case for greater public involvement in syphilis control and prevention programs. Urgent action is needed to prioritize syphilis control in a wide range of settings.